Fabrication of graphene oxide aerogels loaded with catalytic AuPd nanoparticles. (March 2015) - Tang, Mingyi; Wu, Tao; Na, Heya; Zhang, Sai; Li, Xianxian; Pang, Xiaobo
Graphical abstract: Highlights: Au–Pd/GO by reducing AuCl4 −1 and PdCl4 −2 with GO without any additional reductant. The Au–Pd/GO aerogels were prepared by the unidirectional freeze–drying method. The obtained aerogels had an ordered porous construction. The aerogels show high catalytic activity for the reduction of 4-nitrophenol. The aerogels show good recyclability for the reduction of 4-nitrophenol. Abstract: Au–Pd nanoparticles were deposited on the graphene oxide (GO) nanosheets to form Au–Pd/GO nanocomposites by simultaneously reducing AuCl4 − and PdCl4 2− with GO without the use of any additional reductant. The Au–Pd/GO nanocomposites were used to fabricate dimensional Au–Pd/GO aerogels by a simple and green method, unidirectional freeze–drying method. The obtained Au–Pd/GO aerogel has an ordered porous architecture and shows high catalytic activity and good recyclability in a model reaction, reduction of 4-nitrophenol.